2013
DOI: 10.1113/jphysiol.2013.254300
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous responses of nucleus incertus neurons to corticotrophin‐releasing factor and coherent activity with hippocampal theta rhythm in the rat

Abstract: Key points• The nucleus incertus (NI) is a stress and arousal responsive, hindbrain region involved in ascending control of septohippocampal theta rhythm.• NI neurons express high levels of the neuropeptide relaxin-3 and corticotrophin-releasing factor (CRF) receptor-1 (CRF-R1).• We report the first in-depth characterization of NI neurons, using in vivo and in vitro electrophysiological techniques, which reveal a population of relaxin-3-containing NI neurons activated by CRF via postsynaptic CRF-R1 and a non-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
155
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 87 publications
(164 citation statements)
references
References 61 publications
7
155
0
2
Order By: Relevance
“…The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25]. Anatomical and functional data [15][16][17][18] suggest that relaxin-3/RXFP3 systems may interact directly with monoamine [19,26] and other peptide systems [27][28][29], and/or act at shared downstream limbic and hypothalamic target areas to modulate 'anxiety' and other stress-related responses [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The neuroanatomy of the relaxin-3/RXFP3 system suggests a broad role as an ascending neuromodulatory network [20,21], akin to the monoamine systems including serotonin, and noradrenaline [22][23][24][25]. Anatomical and functional data [15][16][17][18] suggest that relaxin-3/RXFP3 systems may interact directly with monoamine [19,26] and other peptide systems [27][28][29], and/or act at shared downstream limbic and hypothalamic target areas to modulate 'anxiety' and other stress-related responses [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Rxfp3-KO and wild-type littermate mice display similar serum corticosterone concentrations at baseline and after acute restraint stress As our acute RXFP3-A2 injection studies may have been somewhat confounded by the stress stimulus associated with the protocol, and in light of earlier evidence suggesting links between relaxin-3 signalling and stress-responses and CRH related signalling Lenglos et al 2013;Ma et al 2013;Lenglos et al 2015), we used a characterised strain of whole-of-life (null) Rxfp3 KO mice (Hosken et al 2015) to investigate whether a global deletion of RXFP3 from the brain altered basal corticosterone levels in serum, and whether the HPA axis associated increase in corticosterone levels in response to acute stress would be altered in these mice.…”
Section: Resultsmentioning
confidence: 81%
“…Sections from Crh-IRES-Cre;Ai14 were incubated with a characterised monoclonal relaxin-3 antibody (a 1:5 dilution of cell culture media) raised against an N-terminal region of the mature relaxin-3 peptide in mouse (Kizawa et al 2003;Ma et al 2013), whereas sections from colchicine-treated C57BL/ 6J mice were incubated with anti-relaxin-3 (1:5) and a 1:500 dilution of a specific rabbit anti-CRH antibody (kindly provided by the Wylie Vale Laboratory, Salk Institute, San Diego, USA). Antibodies were diluted in a 2% NHS and 0.1% Triton X-100 in PB solution, and sections were incubated for 48 h at 4°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…CRF infusion into, or electrical stimulation of, the NI impairs long-term potentiation (LTP) of hippocampal-medial prefrontal cortical synapses 11 , whereas intra-NI infusion of the CRFR1 antagonist antalarmin reversed stress-induced suppression of LTP in this pathway 12 . Intra-NI infusion of the CRFR1 antagonist CP-376395, but not the CRFR2 antagonist astressin 2B, considerably reduced the reinstatement of alcohol seeking in rats that was induced by administration of the pharmacological stressor yohimbine 13 -an effect that is probably mediated by CRFR1 activation of relaxin-3-positive NI neurons 6,14 . The NI is therefore a stressresponsive nucleus and, through CRFR1, contributes to memory and learning, stressinduced reward seeking, impairments in neuronal plasticity, and arousal behaviours [9][10][11][12][13] .…”
mentioning
confidence: 99%
“…This highly conserved structure consists mainly of GABAergic projection neurons, innervates many forebrain regions 3 and has been implicated in various behaviours including arousal and responses to stress 2,4 . NI neurons express CRF receptor type 1 (CRFR1) protein and mRNA in abundance 5 , and electrophysiological characterization in vitro and in vivo has revealed that CRF depolarizes NI cells via postsynaptic CRFR1 in a long-lasting and non-desensitizing manner 6 . Substantial evidence confirms the importance of CRF signalling in the NI in relation to various stress-related disorders, such as anxiety (reviewed in REFS 2,7).…”
mentioning
confidence: 99%